Implementation of the COSO ERM-Based Internal Control System in Marketing Management at Bank Mandiri - Al Rasyid, Dwiyan; Suryanugraha, Dim Zarita; Syaiful, Rizal Fahmi; Lestari, Nadya Ayu; Hilman, Nadia Ulfa Agustin; Nisa, Ana Sakinatun; Adam, Asep Muhammad (PT. Riset Press International, 2025)
The Internal Control System (ICS) is a crucial element in ensuring that an organization's objectives are achieved effectively and efficiently, maintaining the integrity of financial reports, protecting organizational assets, and ensuring compliance with applicable regulations. This study aims to evaluate the effectiveness of implementing ICS based on the COSO Model Enterprise Risk Management (ERM) components at Bank Mandiri KCP Cikurubuk, Tasikmalaya. The methodology used in this study is a qualitative approach with a case study, where data was collected through in-depth interviews, documentation, and observations of the ICS application in marketing procedures and policies. The results of the study indicate that the implementation of ICS at Bank Mandiri KCP Cikurubuk has been running well and is relatively effective in controlling risks and monitoring performance. In particular, the supervision of marketing policies has been in accordance with the established procedures, and there has been adequate follow-up by the Government Internal Supervisory Apparatus (APIP) to maintain the sustainability of this effectiveness. The conclusion of this study is that the ICS implemented at Bank Mandiri KCP Cikurubuk is effective and efficient in supporting the achievement of organizational goals, as well as providing a solid foundation for better internal supervision in the future.